Sagot :
Explications étape par étape :
a = 5√2 - 3√2
⇔ a = 2√2
b = 2√7 + √7
⇔ b = 3√7
c = √10 + 5√10
⇔ c = 6√10
d = √2 + 3√5 - 2√2 + √5
⇔ d = √2 - 2√2 + 3√5 + √5
⇔ d = -√2 + 4√5
Ecrire sous forme a√b
√90 . √40 . √250 . √8 . √18 . √32 . √48 . √75 . √300
Décomposons chaque radicande en facteurs premiers
⇔ √2. 3².5 * √2³.5 * √2 . 5³ * √2³ * √2.3² * √2⁵ * √2⁴.3 * √3.5² * √2².3.5²
⇔ 3√2.5 * 2√2.5 * 5√2.5 * 2√2 * 3√2 * 4√2 * 4√3 * 5√3 * 2.5√3
⇔ 3√10 * 2√10 * 5√10 * 2√2 * 3√2 * 4√2 * 4√3 * 5√3 * 10√3
⇔ 60 * 5√10 * 12 * 4√2 * 60 * 10√3
⇔ 300√10 * 48√2 * 600√3
⇔ 14400√20 * 600√3
⇔ 8 640 000 √60
⇔ 8 640 000 √2².3.5
⇔ 17 280 000√15
e = 2√90 + √40
⇔ e = 2.√2. 3².5 + √2³.5
⇔ e = 2. 3√2.5 + 2√2.5
⇔ e = 6√10 + 2√10
⇔ e = 8√10
f = √8 + √18
⇔ f = √2³ + √2.3²
⇔ f = 2√2 + 3√2
⇔ f = 5√2
c = √75 - √300
⇔ c = √3.5² - √2².3.5²
⇔ c = 5√3 - 10√3
⇔ c = -5√3
d = 2√48 + 3√32
⇔ d = 2.√2⁴.3 + 3.√2⁵
⇔ d = 2.2²√3 + 3.2²√2
⇔ d = 2³√3 + 12√2
⇔ d = 8√3 + 12√2
e = √8 * √18
⇔ e = 2√2 * 3√2
⇔ e = 6√4
f =√48 * √32
⇔ f = 4√3 * 4√2
⇔ f = 16√6